Evaluación al Control Interno en la emisión, manejo y recaudación Ilustre Municipio del Cantón Guano, período enero a diciembre del 2009, para la optimización de los recursos. - Lara Carillo, Zoyt Renata (2011)
It is worthy to consider this summary of a project entitled "INTERNAL CONTROL EVALUATION IN THE ISSUANCE, MANAGEMENT AND FUND-valued goods and claims CANTON TOWNSHIP OF DISTINGUISHED GUANO, DICEIMBRE PERIOD JANUARY OF 2009 FOR THE OPTIMIZATION OF RESOURCES ", in which the problem statement evidenced the need to promote their social partners on a genuine process of modernization for the control of valued species Revenue Unit of the Municipality, and aims to: 1) maintain adequate control; 2) Analysis of Canton Township and Illustrious Guano Guano, 3) Study of the components of internal control within the rental unit, 4) Creating mandatory within the rental unit to maintain a computer system connected to the whole system to handle network. According to the methodology used for this research based methods, techniques and instruments to operationalize the research object, to finally reach the following conclusions: using the diagnosis applied to the Illustrious Municipality of Guano, it was evident deficiencies in the management and control activities, namely the issuance of spices valued at not aware that numbers are numbers that have been issued, plus calculations are inaccurate because they do it manually so you do not have anyone they control the costs of permits and others. In another of the conclusions that are not connected to the financial system that manages the municipality as obtain accurate and reliable values. According to interviews with employees of the Revenue Unit does not have a clear understanding of what internal control is not so applied within the institution.